2004
DOI: 10.1128/aac.48.6.2298-2301.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Erythromycin Resistance in Oral Bacteria

Abstract: We determined the prevalence of erythromycin-resistant bacteria in the oral cavity and identified mef and erm(B) as the most common resistance determinants. In addition, we demonstrate the genetic linkage, on various Tn1545-like conjugative transposons, between erythromycin and tetracycline resistance in a number of isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
4
22
0
Order By: Relevance
“…The high prevalence of TET resistance in oral E. faecalis could be the result of the promiscuous spread of tet(M) containing Tn916-related elements within oral microbiota, while our data do not allow further speculations on this. To sum up, our observations are consistent with the general recognition of oral microflora as an important reservoir for antimicrobial resistance (30,42,43).…”
Section: Discussionsupporting
confidence: 90%
“…The high prevalence of TET resistance in oral E. faecalis could be the result of the promiscuous spread of tet(M) containing Tn916-related elements within oral microbiota, while our data do not allow further speculations on this. To sum up, our observations are consistent with the general recognition of oral microflora as an important reservoir for antimicrobial resistance (30,42,43).…”
Section: Discussionsupporting
confidence: 90%
“…Differences in restriction patterns of mobile ele- ments have been reported previously, e.g. with Tn1545 elements [13]. The amplified products of int 916 , int 5252 , umuC and umuD from these five isolates were sequenced (sequences listed under accession nos.…”
Section: Forward Primermentioning
confidence: 98%
“…The oral microflora is an important reservoir for transferable antimicrobial resistance [1], [2], [3], [4]. Our previous study of oral Enterococcus faecalis isolated from Norwegian patients with marginal and apical periodontitis showed that approximately 50% of the strains were resistant to one or more of the tested antimicrobial agents, mostly tetracycline and/or erythromycin [5], [6].…”
Section: Introductionmentioning
confidence: 99%